Argentina - Increasing Utilization of Health Care Services among the Uninsured Population : The Plan Nacer Program - Cortez, Rafael; Romero, Daniela (World Bank, Washington, DC, 2013)
This paper describes the functioning and performance of Argentina's Provincial Maternal and Child Health Investment Program, commonly referred to as Plan Nacer. The program is aimed at increasing access - for uninsured pregnant women and children under six years old - to a basic set of health services known to effectively address the main causes of maternal and child mortality, while improving the effectiveness and efficiency of the health system. The program supports the development and implementation of publicly funded provincial maternal and child health insurance and the introduction of highly innovative results-based financing mechanisms at the national, provincial, and provider levels. This document is organized as follows. Section 2 provides an overview of the Argentine health care system, including a description of public health, primary care, and supply-side efforts, to put in context the implementation of Plan Nacer. Section 3 presents a detailed description of the main features of the program, including the institutional architecture; the targeting, identification, and enrolment of beneficiaries; the management of the program's funds and benefits package; and the information environment of Plan Nacer. Section 4 provides a discussion of the highly innovative results-based financing mechanisms included in the design of the program. Section 5 draws some conclusions on the pending agenda and challenges ahead.